Informal Virtual Mentoring for Team Leaders and Members: Emergence, Content, and Impact. (August 2016) - Hart, Rama Kaye
The Problem: Leaders and members of virtual teams do not always have the opportunity to seek training and development to overcome the challenges of being culturally and geographically distant, nor the serendipitous exchanges afforded by proximity to work associates who might provide mentoring for personal or professional guidance. How then might organizations and human resource development (HRD) professionals foster relationships that are supportive in nature, considered critical for many outcomes associated with individual and leadership development and virtual team success? The Solution: Drawing on the theoretical perspective that communication is constitutive of social, psychological and organizational realities, a conceptual model was developed through an interpretive study. The model highlights how informal developmental relationships emerge, what type of communication constitutes these relationships, and the impact they have on leaders and members of virtual work teams. The Stakeholders: The results of this study have implications for leaders and members who work virtually and for HRD professionals seeking strategies to create and improve informal developmental relationships through the medium of virtual work team communication. Opportunities exist for researchers to explore the effectiveness and outcomes of building developmental relationships in virtual contexts.